Implementasi Super Enkripsi Menggunakan Metode Rail Fence Cipher dan Metode Caesar Cipher Pada Data Pasien Klinik Eka Karigas - Fernando, Fery; Pakereng, Magdalena A. Ineke (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Data security is considered very important in nowadays information technology era to minimize data theft. To achieve data security, an encoding process for the data is needed. The encryption process can use a super encryption scheme by combining two or more cryptographic techniques to provide double security. In this research intend to implement the Rail Fence Cipher and Caesar Cipher cryptographic algorithms by using a super encryption scheme on patient data at the Eka Karigas Clinic. The combination of these two cryptographic algorithms is able to provide security by using encryption techniques on patient data at the Eka Karigas Clinic and returning it using a decryption technique to its original form so as not to cause data integrity loss.